Influence of self-efficacy on career exploration behaviours among Malaysian young adolescent - Zainudin, Zaida Nor; Engku Kamarudin, Engku Mardiah; Rong, Lee Wei; Asri, Alia Sarah (South East Asian Association for Institutional Research, 2024)
Education professionals, including teachers and school counselors, have long been drawn to studies on students' self-efficacy and career exploration behaviors. Career development theories have shown that career exploration begins in the teenage years; however, studies on self-efficacy and career exploration mainly targeted the tertiary education sample group and are rarely found within the Malaysian secondary school student group who are about to enter tertiary institutions. This study set out to investigate the connection between upper secondary students' self-efficacy and career exploration. The difference between school grades and career exploration was also examined. The quantitative-correlational research was carried out using a self-reported survey among secondary students. A stratified random sampling method was employed to obtain 219 respondents. Descriptive analysis was used to investigate high career exploration behaviors among secondary school students. Pearson correlation showed a positive correlation between selfefficacy and career exploration. Meanwhile, linear regression analysis reported that self-efficacy significantly predicted career exploration. Lastly, the ANOVA result showed a significant difference in the career exploration behaviors among all school grades. Among the respondents, Form 4 students had higher career exploration behaviors than Form 3 and Form 5 students. The results of this study indicated that self-efficacy plays a significant role in predicting career exploration; hence, recommendations were made for school counselors to guide students in their career exploration. The implications highlighted the role of higher education institutions in designing more comprehensive career exploration interventions to prepare students at both pre-university and university levels.